MANAGEMENT OPERATIONS FISHING BOATS IN THE VILLAGE CHART sackcloth Bay PASALABAN DISTRICT CITY WEST SUMATRA PADANG - Darmawan '; Pareng Rengi; Alit Hindri Yani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This study was conducted in December 2015 in the village Pasalaban sackcloth Bay District of the city of Padang of West Sumatra Province. Aiming to analyze the management of fishing operations fishing gear chart boats operated in the waters around the village Pasalaban sackcloth Bay districts. The method used in this study is a survey method, namely observation and retrieve data directly into an object of research. The results of the analysis of the operational management of the arrest, charts boat fishing business has been quite good, where the business is in compliance with such management functions.Keywords: Boats chart boats, Management, PPS Bungus